2014
DOI: 10.1186/1472-6831-14-123
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malocclusion and its association with dental caries among 12-18-year-old disabled adolescents

Abstract: BackgroundTo assess the prevalence of malocclusion among 12-18-year-old disabled adolescents in Chennai, Tamil Nadu, India, by using the Dental Aesthetic Index (DAI) and to determine the association of malocclusion with dental caries.MethodsThis cross-sectional study included 243 children with various mental disabilities with or without physical infirmities. The Dental Aesthetic Index (DAI) and the dentition status were recorded using the World Health Organization Oral Health Surveys – Basic Methods (1997) Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
4
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 27 publications
4
46
4
9
Order By: Relevance
“… (41.2%) but higher than the percentage reported by Vellappally et al. of 5.6% in similar populations. However, 18.8% require urgent treatment also lower in comparison to Onyeaso study of 32%.…”
Section: Discussionmentioning
confidence: 57%
“… (41.2%) but higher than the percentage reported by Vellappally et al. of 5.6% in similar populations. However, 18.8% require urgent treatment also lower in comparison to Onyeaso study of 32%.…”
Section: Discussionmentioning
confidence: 57%
“…A study done by Vellappally et al (18) with children with several syndromes, including CP, DS and intellectual deficit , concluded that, of the 243 examined children, 93% presented some form of malocclusion requiring orthodontic treatment. The most common malocclusion was crowding of anterior teeth in 84.8%, followed by anterior mandibular irregularity ≥1mm, in 77.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Essa realidade pode determinar índices expressivos das doenças cárie e periodontal, as quais podem exercer influência negativa sobre a qualidade de vida desses indivíduos [6][7][8][9][10] .…”
Section: Discussionunclassified